Pengaruh Kepemimpinan Lurah Terhadap Kesadaran Masyarakat Dalam Membayar Pajak Bumi Dan Bangunan Di Kelurahan Tempe Kabupaten Wajo - Nurmalia Gani; Burhanuddin Burhanuddin (Jurnal Bintang Manajemen, 2024)
Land and Building Tax (PBB) is a direct tax collected by the central government but the revenue is reflected for the benefit of the community in the area concerned with the location of the tax object. Considering the important role of the community in covering state financing, the influence of the Village Head's leadership is needed to be able to utilize the potential of Land and Building Tax in the area and motivate the apparatus and the community to be able to carry out their obligations in paying taxes. The existence of the majority of people who do not fulfill their obligation to pay PBB is automatically an obstacle in tax collection, but this is because people are less aware of paying taxes, or even do not know the function of paying taxes themselves.